Entrepreneurs as discoverers: the case of portuguese born globals - Dominguinhos, Pedro (2002)
Traditionally, internationalisation has been study has a gradual process, where the firms start their operation to close markets with forms involving low risk. As time goes by, and the firm acquire experiential knowledge, the firm change his commitment to internationalisation, using more risky and demanding entry modes, and acting in distant markets. In the nineties, several firms, labelled born globals, challenge this pattern, operating, since inception, in international markets, start in distant markets and using hybrid entry modes, as alliances, licenses and franchising. This paper, through four in depth case studies, of Portuguese born globals, shows that entrepreneurs act as discoverers and are the key element in understanding this phenomenon. It also shows that prior knowledge corridors are crucial for entrepreneurs, in his process of discovery and exploitation of opportunities.